MENALAR ULANG USHUL FIKIH MAJELIS ULAMA INDONESIA (MUI) DALAM KONTEKS KEINDONESIAN - Siti Khoirotul Ula (Jember: Sharia Faculty State Islamic University of Kiai Haji Achmad Siddiq Jember, 2020)
This paper is concerned with the study of the reasoning of the Ushul Fiqh of the Indonesian Ulama Council (MUI) in the Indonesian context. By the content analysis approach through reading of some of the MUI fatwas, it was concluded that the ushul fiqh foundation used by the MUI was like the mainstream typology of Islamic law, namely the ushul fiqh method commonly used by mutakallimin and fuqaha. However, in relation to fatwas related to contemporary issues, the sad adz-dzariah theory is more dominant than other theories. Another thing found from the study of the MUI fatwas in relation to methodology is the tendency of the MUI fatwas towards the way of bayani reasoning or textualism.